2002
DOI: 10.1136/oem.59.9.620
|View full text |Cite
|
Sign up to set email alerts
|

Validity of empirical models of exposure in asphalt paving

Abstract: Aims: To investigate the validity of empirical models of exposure to bitumen fume and benzo(a)pyrene, developed for a historical cohort study of asphalt paving in Western Europe. Methods: Validity was evaluated using data from the USA, Italy, and Germany not used to develop the original models. Correlation between observed and predicted exposures was examined. Bias and precision were estimated. Results: Models were imprecise. Furthermore, predicted bitumen fume exposures tended to be lower (−70%) than concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…The cumulative distributions suggest that VOC exposure typically varies about three-to four-fold between persons in a given city, but varies more than 20-fold in about a quarter of the cases. These systematic differences in exposure to a particular VOC across city residents can be identified and used for epidemiological purposes in much the same manner that tasks or work locations are exploited to assign groups in occupational epidemiology (e.g., see Burstyn et al, 2002, Kromhout et al, 1994;Kromhout and Heederik, 1995). Nonetheless, Hoffmann et al (2000) reported models that explained 39% of the variation in environmental exposure levels for benzene and 60% of the variation in exposure levels for ethylbenzene and the xylenes.…”
Section: Comparisons Between Environmental and Occupational Exposuresmentioning
confidence: 99%
“…The cumulative distributions suggest that VOC exposure typically varies about three-to four-fold between persons in a given city, but varies more than 20-fold in about a quarter of the cases. These systematic differences in exposure to a particular VOC across city residents can be identified and used for epidemiological purposes in much the same manner that tasks or work locations are exploited to assign groups in occupational epidemiology (e.g., see Burstyn et al, 2002, Kromhout et al, 1994;Kromhout and Heederik, 1995). Nonetheless, Hoffmann et al (2000) reported models that explained 39% of the variation in environmental exposure levels for benzene and 60% of the variation in exposure levels for ethylbenzene and the xylenes.…”
Section: Comparisons Between Environmental and Occupational Exposuresmentioning
confidence: 99%
“…We reconstructed personal beryllium exposure estimates for an epidemiologic study at a beryllium manufacturing facility (4) and validated those estimates. Although reconstructed beryllium exposure tended to be slightly higher than the measured mean, it is important to note that the overestimation of reconstructed exposures would lead to underestimated risk per unit of exposure (16,39). Furthermore, any biases in reconstructed exposure estimates in this study were non-differential (unrelated to outcome status), which would attenuate the exposure-response relationship, but the magnitude of the attenuation cannot be estimated (39).…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, Hornung et al (15) reported an overall relative bias of -24% in a model used to predict ethylene oxide exposures, when compared to an internal validation dataset. Burstyn et al (16) used external datasets obtained from the different countries to validate exposure estimates from a model for benzo(a)pyrene in asphalt paving. They found weak correlation (r p =0.28) and high relative bias (approximately -70% to -50%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The contextual information coded for each exposure measurement included production characteristics within a job (using a classification similar to that used in the company questionnaire), repeated measurements within a worker, and country. We constructed 4 14 and validated 15 mixed-effects exposure assessment models, with production characteristics as fixed effects and repeated measurements on the same worker as random effects, to predict quantitative exposures to benzo(a)pyrene among asphalt paving workers. Use of coal tar was the strongest determinant of exposure to benzo(a)pyrene, but time period, mastic laying, re-paving, surface dressing and oil gravel paving were also important predictors.…”
Section: Exposure Assessmentmentioning
confidence: 99%